Broadband reflection in polymer-stabilized cholesteric liquid crystal film with zinc oxide nanoparticles film thermal diffusion method. Issue 14 (14th November 2021) - Gan, Ping; Zhang, Xuetao; Zhao, Limin; Shi, Weiting; Cao, Hui; Wang, Huihui; Yang, Zhou; Wang, Dong; He, Wanli
ABSTRACT: Broadband reflective films were prepared by thermal diffusion of zinc oxide nanoparticles (ZnO NPs) in chiral nematic liquid crystals (N*-LCs). Ultraviolet (UV) light was irradiated in the direction of the thickness of the liquid crystal film to form the intensity gradient of UV light, to induce the gradient distribution of the pitch. The effects of the content of ZnO NPs, the UV light intensity, the UV irradiation time, the monomer concentration, and the diffusion temperature on the reflective bandwidth of the sample were studied. The results show that the appropriate content of ZnO NPs and the effective UV radiation intensity is beneficial to the broadband reflection of the sample. To elucidate the mechanism of photoinduced pitch gradients, the fracture surface of the sample film was observed by scanning electron microscopy (SEM), and the influence of experimental conditions on the broadband reflection performance of N*-LCs films was analysed theoretically. GRAPHICAL ABSTRACT: uf0001a